Iron catalyst for decomposition of methane: Influence of Al/Si ratio support - Ahmed S. Al-Fatesh; Ahmed A. Ibrahim; AbdulAziz M. AlSharekh; Fawaz S. Alqahtani; Samsudeen O. Kasim; Anis H. Fakeeha (Egyptian Journal of Petroleum)
20% iron catalysts supported on combined alumina and silica through different proportions (Al2O3:SiO2: 100:0.00, 90.0:10.0, 80.0:20.0 and 0.0:100.0) were tested for the catalytic decomposition of methane to produce H2 and carbon. The catalysts were prepared via impregnation technique. The physicochemical properties of the catalysts were characterized with TGA, XRD, H2-TPR, and TEM techniques. The results specified no reaction for all temperatures when the catalysts were supported with bare silica. Indeed, the 20%Fe/(Si-80)-800 catalyst with 20% silica support operated at 800 °C produced CH4 conversion profile that rapidly descended from 64% to 5% due to the high content of silica. Plain alumina supported catalyst demonstrated the best conversion and stability operated at 800 °C. The CH4 conversion started from 83.4% and lasts at 82.2% after 300 min on stream. Keywords: Alumina, Fe catalyst, Hydrogen production, Methane decomposition, Silica